2017
DOI: 10.1055/s-0042-117722
|View full text |Cite
|
Sign up to set email alerts
|

Energy Systems Contribution in the Running-based Anaerobic Sprint Test

Abstract: The aims of the present study were to verify the contributions of the energy systems during repeated sprints with a short recovery time and the associations of the time- and power-performance of repeated sprints with energetic contributions and aerobic and anaerobic variables. 13 healthy men performed the running-based anaerobic sprint test (RAST) followed by an incremental protocol for lactate minimum intensity determination. During the RAST, the net energy system was estimated using the oxygen consumption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 45 publications
3
44
0
5
Order By: Relevance
“…A significant moderate relationship was also found here between mean time in the 40-m MSRT court test and VO 2max derived from laboratory treadmill test (r = − 0.58). There is evidence in the literature that, although the aerobic pathway might not possibly be the determining factor to reach optimal performance in repeated highintensity running efforts with only brief rests, some experiments (in male or female subjects) indicates that proper development of aerobic metabolism can aid during recovery periods between bouts, being positively related to phosphocreatine resynthesis, a limiting factor for the repeated-sprint ability [50,52]. Therefore, ensuring a high aerobic power in professional female futsal players may contribute to performing high-intensity running efforts interspersed with short recovery times.…”
Section: Discussionmentioning
confidence: 99%
“…A significant moderate relationship was also found here between mean time in the 40-m MSRT court test and VO 2max derived from laboratory treadmill test (r = − 0.58). There is evidence in the literature that, although the aerobic pathway might not possibly be the determining factor to reach optimal performance in repeated highintensity running efforts with only brief rests, some experiments (in male or female subjects) indicates that proper development of aerobic metabolism can aid during recovery periods between bouts, being positively related to phosphocreatine resynthesis, a limiting factor for the repeated-sprint ability [50,52]. Therefore, ensuring a high aerobic power in professional female futsal players may contribute to performing high-intensity running efforts interspersed with short recovery times.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the main question is no longer whether genes are associated with the elite athletic status, but rather with the genetic profile contributing most to extraordinary results in sports. The majority of studies have concentrated on genotyping of individuals at physiological end-points of the athletic performance -in "endurance" and "power" sport disciplines, overlooking the fact that the majority of sport disciplines nowadays can be labelled as "mixed energy system" sports (Milioni et al 2017). Although multiple genetic variants in various genes are thought to influence muscle function and physical performance, here we focus on two common gene polymorphisms trying to explain blood pressure variations in a group of Serbian elite male athletes from either endurance, power or mixed sports.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the information above, the importance of understanding which factors may be associated with the improvement of RSA becomes evident. From the point of view of energy demand, despite a greater anaerobic contribution in RSA 11,12 , previous studies have reported the importance of aerobic fitness in RSA performance, and a significant and negative correlation with greater aerobic power 13,14 was found. These authors have argued that this relationship is mainly due to the importance of oxidative metabolism in providing adenosine triphosphate (ATP) for resynthesis of phosphocreatine (PCr) and removal of metabolites (H + and [P i -]) 5 .…”
Section: Introductionmentioning
confidence: 86%
“…In this context, previous studies have shown that the PCr resynthesis rate is dependent on the oxygen supply 15,16 . Additionally, it was reported that as sprints repeat, the aerobic contribution to energy supply is greater 11,17 , which may delay the onset of fatigue 18 .…”
Section: Introductionmentioning
confidence: 99%